Impact of apixaban on routine and specific coagulation assays: a practical laboratory guide - Douxfils, Jonathan; Chatelain, Christian; Chatelain, Bernard; Dogné, Jean-Michel; Mullier, François (Thrombosis and Haemostasis, 2013)
Apixaban does not require monitoring nor frequent dose adjustment. However, searching for the optimal dose for the individual patient may be useful in some situations. Moreover, there is a need for clinicians to know whether coagulation assays are influenced by apixaban use. The aim of this study was to determine which coagulation assay could be used to assess the impact of apixaban on haemostasis and provide good laboratory recommendations for the accurate interpretation of haemostasis assays. Apixaban is spiked at concentrations ranging from 5 to 500 ng/ml in platelet-poor plasma. Routinely used or more specific coagulation assays are tested. Results show a concentration dependent prolongation of aPTT, PT and dilute PT. The sensitivity mainly depends on the reagent, but none of these tests is sensitive enough to ensure an accurate estimation of the pharmacodynamic effect of apixaban. FXa chromogenic assays show high sensitivity and a linear correlation depending on the reagent and/or the methodology. Immunological assays and assays acting below the FXa are not influenced by apixaban. In conclusion, PT and/or dilute PT cannot be used to assess apixaban pharmacodynamic properties. More specific and sensitive assays such as chromogenic FXa assays using specific calibrators are required. In case of thrombophilia or in the exploration of a haemorrhagic event, immunological assays should be recommended, when applicable. Standardisation of the time between the last intake of apixaban and the sampling is mandatory.
Keywords: Apixaban; monitoring; coagulation assays; assessment; laboratory recommendations